Environmental Moral Conscience: Relevance of School Mediation - Sánchez, Henry; Balaguer Dávila, Carlos (Rastros Rostros, 2012)
Paper derived from research “Environmental Moral Conscience from School: Transforming Attitudes for Sustainability”, held in 2012 at the Universidad del Tolima. This research aims to show the latent social need to have conscious individuals committed with sustainable development, and directs the efforts of education at the search for coherent strategies. In this regard, environmental education is responsible for cognitive and practical aspects, but shows little effect in changing attitudes, values and sustainable behaviors. For these elements to effectively integrate into the individual’s autonomy, it is proposed to integrally relate them to their moral and attitudinal development. To this end, this study proposes the application of mediations and the implementation of a pilot test in place to confirm the results of the intervention.
Keywords: eco-friendly attitude; sustainable behavior; environmental moral development; didactic proposal